2017
DOI: 10.1155/2017/5846368
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Osteoid Osteoma as a Cause of Anteromedial Knee Pain

Abstract: A 32-year-old male patient presented to our clinic with chronic left knee pain that was ongoing for about 1.5 years. The patient visited several times our clinic and the other clinics; conservative treatment (including rest, knee brace, and ice application with NSAIDs) was recommended by various different doctors. The anamnesis, physical examination, and plain radiography were nonspecific. Early MRI findings mislead us to believe it is bone marrow edema. One and half years with noneffective treatment, the knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Intraarticular localization of osteoid osteoma is one condition that complicates the diagnosis and is frequently associated with delayed or misdiagnosis. Sagtas et al 6 reported a case of intraarticular osteoid osteoma in an adult male with a 1.5-year history of nonspecific pain. Conservative treatment, including rest, knee brace, and ice application with NSAIDs, was not effective.…”
Section: Discussionmentioning
confidence: 99%
“…Intraarticular localization of osteoid osteoma is one condition that complicates the diagnosis and is frequently associated with delayed or misdiagnosis. Sagtas et al 6 reported a case of intraarticular osteoid osteoma in an adult male with a 1.5-year history of nonspecific pain. Conservative treatment, including rest, knee brace, and ice application with NSAIDs, was not effective.…”
Section: Discussionmentioning
confidence: 99%
“…Assoun et al [ 26 ] report that CT scan proved to be more accurate than MRI in detection of the nidus in 63% of cases. Also, CT scans proved to be a valuable tool in preoperative planning of the surgery[ 29 ]. Therefore, we have performed a CT scan in three of our patients.…”
Section: Discussionmentioning
confidence: 99%